2017
DOI: 10.1007/s00127-017-1386-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of parental migration on Chinese children’s psychosocial well-being: mitigating and exacerbating factors

Abstract: PurposeProlonged separation from migrant parents raises concerns for the well-being of 60 million left behind children (LBC) in rural China. This study aimed to investigate the impact of current and previous parental migration on child psychosocial well-being, with a focus on emotional and behavioral outcomes, while considering factors in family care and support.MethodsChildren were recruited from schools in migrant-sending rural areas in Zhejiang and Guizhou provinces by random stratified sampling. A self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
6
60
0
Order By: Relevance
“…First, the negative association between family resources and mental health addressed the seemingly inconsistent findings on the impact of parental migration on LBC's mental health. On the one hand, numerous studies have documented that LBC tend to experience symptoms of depression (J. Guo et al, ; Tomsa & Jenaro, ; Y. L. Wu et al, ), social anxiety (Dai & Chu, ; Man et al, ; Shi, Bai, Shen, Kenny, & Rozelle, ; Zhang & Xu, ), and other distress‐related symptoms (Ling et al, ; Su et al, ; Wickramage et al, ; C. Zhao et al, ). On the other hand, several studies indicate that LBC are less likely to experience poor mental health outcomes (Asis, ; Asis & Ruiz‐Marave, ; X. Guo et al, ) and that they tend to fare comparably with or better than non‐LBC (Asis, ; Graham & Jordan, ; Parreñas, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the negative association between family resources and mental health addressed the seemingly inconsistent findings on the impact of parental migration on LBC's mental health. On the one hand, numerous studies have documented that LBC tend to experience symptoms of depression (J. Guo et al, ; Tomsa & Jenaro, ; Y. L. Wu et al, ), social anxiety (Dai & Chu, ; Man et al, ; Shi, Bai, Shen, Kenny, & Rozelle, ; Zhang & Xu, ), and other distress‐related symptoms (Ling et al, ; Su et al, ; Wickramage et al, ; C. Zhao et al, ). On the other hand, several studies indicate that LBC are less likely to experience poor mental health outcomes (Asis, ; Asis & Ruiz‐Marave, ; X. Guo et al, ) and that they tend to fare comparably with or better than non‐LBC (Asis, ; Graham & Jordan, ; Parreñas, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the huge number of labor migrants has raised concerns regarding its social cost to families (Asis, ; Garabiles, Ofreneo, & Hall, ), and particularly to left‐behind children (LBC). A number of studies has shown that children who are left behind by their parents have poor mental health (Hu, Lu, & Huang, ; Ling, Fu, & Zhang, ; Mazzucato et al, 2015; Wen & Lin, ; Wickramage et al, ; C. Zhao, Wang, Li, Zhou, & Hesketh, ) and are likely to be at higher risk of experiencing symptoms of depression (J. Guo et al, ; He et al, ; Tomsa & Jenaro, ; L. Wang et al, ; Y. L. Wu et al, ), anxiety (Dai & Chu, ; Man, Mengmeng, Lezhi, Ting, & Jingping, ; Tomsa & Jenaro, ; Zhang & Xu, ), and social anxiety (Zhang & Xu, ). LBC have also been known to manifest low quality of life (Jia & Tian, ), low life satisfaction and happiness (F. Fan, Su, Gill, & Birmaher, ; Gao et al, ), difficulty in social adjustment (Jia & Tian, ), low self‐concept (X. Wang et al, ), and poor academic performance (Amuedo‐Dorantes & Pozo, ; Asis & Ruiz‐Marave, ).…”
Section: Mental Health Of Children: the Role Of Family As A Resourcementioning
confidence: 99%
“…The non-traditional family structures may be risks for future psychopathology in children [5], and exacerbate the vulnerabilities of children with less social support [6, 7]. Substantial evidence has demonstrated the psychological impact from parental absence.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the parents, carers and children talked of the importance of the Centres as places where homework could be supervised, and they attributed improvements in school performance to this. The inability of grandparents to supervise or help with homework, largely because of their own lack of educational opportunity, has been cited as one of the reasons why LBC fall behind at school in some parts of rural China [ 29 ].…”
Section: Discussionmentioning
confidence: 99%